Third Space of Communication in Soekarno’s Thought - Saintio, Fidelis Aggiornamento; Sujoko, Anang; Sobari, Wawan (Technium Social Sciences Journal, 2021)
Viewed from the perspective of the third space of communication, colonialism is no longer a moment of the West’s domination over the East. The boundary between superiority and inferiority is removed by exchanges of influences. In addition, the third space of communication can also be used as a means of fusing different cultures and values. However, when applied in certain contexts, there are opportunities to enrich the idea of a third space of communication. The enrichment of this idea can be found in the state speech made by President Soekarno on June 1, 1945. Apart from formulating the foundation of the Indonesian state, the speech also aimed to unite the diverse Indonesian peoples into one national identity. Through a hermeneutics analysis, it was found that there was no need to fuse or remove diversity to form a third space of communication